XBX-1 Encodes a Dynein Light Intermediate Chain Required for Retrograde Intraflagellar Transport and Cilia Assembly in Caenorhabditis elegans - Schafer, Jenny C. (The American Society for Cell Biology, 2003)
Intraflagellar transport (IFT) is a process required for flagella and cilia assembly that describes the dynein and kinesin mediated movement of particles along axonemes that consists of an A and a B complex, defects in which disrupt retrograde and anterograde transport, respectively. Herein, we describe a novel Caenorhabditis elegans gene, xbx-1, that is required for retrograde IFT and shares homology with a mammalian dynein light intermediate chain (D2LIC). xbx-1 expression in ciliated sensory neurons is regulated by the transcription factor DAF-19, as demonstrated previously for genes encoding IFT complex B proteins. XBX-1 localizes to the base of the cilia and undergoes anterograde and retrograde movement along the axoneme. Disruption of xbx-1 results in cilia defects and causes behavioral abnormalities observed in other cilia mutants. Analysis of cilia in xbx-1 mutants reveals that they are shortened and have a bulb like structure in which IFT proteins accumulate. The role of XBX-1 in IFT was further confirmed by analyzing the effect that other IFT mutations have on XBX-1 localization and movement. In contrast to other IFT proteins, retrograde XBX-1 movement was detected in complex A mutants. Our results suggest that the DLIC protein XBX-1 functions together with the CHE-3 dynein in retrograde IFT, downstream of the complex A proteins.